Chronic rhinitis in workers at risk of reactive airways dysfunction syndrome due to exposure to chlorine. Issue 5 (1st May 1999) - Leroyer, C; Malo, J L; Girard, D; Dufour, J G; Gautrin, D
Abstract : BACKGROUND: To assess the frequency of chronic upper airways symptoms and to relate the presence of these symptoms to accidental exposure to chlorine and changes in lower airways symptoms, airway function, and bronchial responsiveness in a cohort of workers at risk of sporadic occupational exposure to high concentrations of chlorine. METHODS: Data were collected on symptom assessment, spirometry, and methacholine challenge tests from 211 workers seen twice at a 2 year interval (1992-4). RESULTS: The proportion of workers reporting chronic rhinitis was 46.9% in 1992 and 42.2% in 1994. Chronic rhinitis reported in 1994 was significantly associated with acute exposure to chlorine (self reports, p = 0.02; first aid reports, p = 0.001). In a multivariate logistic regression analysis the presence of reported accidents at the first aid unit (one accident, odds ratio (OR) 3.1, 95% confidence interval (95% CI) 1.3 to 7.5; two or more accidents, OR 6.2, 1.1 to 35.8) and of personal atopy (OR 5.5, 2.2 to 10.8) were significant predictors of chronic rhinitis in 1994. Chronic lower airways symptoms were more frequent in 1994 among workers reporting chronic rhinitis on both assessments than in others (p = 0.03) and changes in bronchial responsiveness were more pronounced in those with persistent rhinitis (p = 0.09). CONCLUSIONS: These results suggest that persistent nasal symptoms in workers at risk of reactive airways dysfunction syndrome could be a useful marker of lower respiratory tract abnormalities.